PENGARUH PEMBERIAN ENZIM PAPAIN PADA PAKAN TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN LELE DUMBO (Clarias gariepinus) Effect of Enzyme Papain Giving Within Food Against Survival and Growth on Dumbo Catfish (Clarias gariepinus) - Sumarwan Syahputra; Syammaun Usman; Rusdi leidonald (AQUACOASTMARINE, 2016)
Intensive Dumbo catfish farming covers the environment, water quality, and feeding. Feeding using the appropriate dose of enzyme papain can determine the growth and survival rate of dumbo catfish. This research aims to know the effect of giving enzyme papain to the catfish and also to determine the amount of enzyme papain which is effective to growth and survival rate of the catfish. This research was conducted from December 2015 - January 2016 in the Laboratory of Aquaculture, Water Resource Management, Faculty of Agriculture, University of North Sumatra. The results showed that the enzyme papain can speed up the length and weight growth of catfish and also increase the survival rate of catfish. The enzyme papain also significantly affects to the growth of length and weight catfish, but it does not have any effect on the survival rate of catfish. The amount of enzyme papain which can effectively affect the length and weight growth of catfish is about 2.5% of the enzyme.Keywords: Catfish, Growth, Cultivation, Survival, Enzyme papain